(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The article studies the cultivation of seedlings from varietal cuttings of mulberry in the conditions of the Tashkent region and the acceleration of the growth and development of cuttings of mulberry by applying a polymer preparation to the cuttings of the cultivated mulberry tree when laying bush plantations, which allows satisfying the needs for feeding the silkworm.